2020
DOI: 10.1002/adem.202000157
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of a Healing Agent by a Water‐Vapor Treatment to Enhance the Self‐Repair Ability of Ytterbium Silicate‐Based Nanocomposite in Multiple Crack‐Healing Test

Abstract: Yb2Si2O7/Yb2SiO5 composites dispersed with silicon carbide (SiC) possess a self‐crack‐healing ability that makes them promising top‐coat materials for multilayered environmental barrier coatings (EBCs) of SiC/SiC gas turbine blades. Stress‐induced surface cracks can be fully healed at high temperatures by the volume expansion of SiO2 glass and the newly formed Yb2Si2O7 in the composite. The reaction between SiO2 and Yb2SiO5 to form Yb2Si2O7 is considered a critical step that determines the high healing efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…Recently, we found that in the SiC/Yb-silicate composites, the healing rate is also influenced by the existence of Yb 2 SiO 5 around the SiC particles, because the monosilicate readily react with the oxidation product of SiC (i.e SiO 2 glass) to form disilicate. This is the reason the apparent activation energy of the crack healing in our SiC nanoparticulate composite (313 kJ/mol) 32) is lower than those of mullite composite (413 kJ/mol) and Al 2 O 3 composite (334 kJ/mol), 33) though our composite were fabricated with smaller amount of SiC (10 vs. 15 vol %). On the other hand, Vu and Nanko, investigated yttrium silicate/SiC composites and found that the monosilicate/disilicate ratio (Y 2 SiO 5 /Y 2 Si 2 O 7 ) determines the level of the activation energy: the larger amount the monosilicate is in the composite, the lower the activation energy.…”
Section: (C) and 5(d)mentioning
confidence: 82%
See 1 more Smart Citation
“…Recently, we found that in the SiC/Yb-silicate composites, the healing rate is also influenced by the existence of Yb 2 SiO 5 around the SiC particles, because the monosilicate readily react with the oxidation product of SiC (i.e SiO 2 glass) to form disilicate. This is the reason the apparent activation energy of the crack healing in our SiC nanoparticulate composite (313 kJ/mol) 32) is lower than those of mullite composite (413 kJ/mol) and Al 2 O 3 composite (334 kJ/mol), 33) though our composite were fabricated with smaller amount of SiC (10 vs. 15 vol %). On the other hand, Vu and Nanko, investigated yttrium silicate/SiC composites and found that the monosilicate/disilicate ratio (Y 2 SiO 5 /Y 2 Si 2 O 7 ) determines the level of the activation energy: the larger amount the monosilicate is in the composite, the lower the activation energy.…”
Section: (C) and 5(d)mentioning
confidence: 82%
“…The lowest annealing temperature that can activate healing behavior in a SiC/Yb-silicate composite is 800°C, as confirmed in the previous study. 32) Therefore, in this research, the composites dispersed with 20 vol % SiC were annealed at 800°C, for 15 min.…”
Section: Characterization and Measurementsmentioning
confidence: 99%
“…The oxidation of a healing agent, an essential step in the healing process, will not occur when temperature is lower than a particular point (e.g. 800 °C for SiC 9) ). Therefore, the quest for finding an alternative healing agent that can be oxidized actively in mid-range temperatures (400-800 °C) is in demand.…”
Section: Introductionmentioning
confidence: 99%